A Study of the Personality and Actions of Qays ibn Sa’d ibn Ubadah Ansari - ALIZADEH, RAMIN; GOLJAN, MAHDI (The journal of contemporary issues in business and government, 2021)
Qays ibn Sa’d ibn Ubadah Ansari is one of the companions of the Prophet (PBUH) and one of the companions of Imam Ali (PBUH) and Imam Hassan (PBUH). There is no date for his birth, but according to current research, upon the entrance of the Prophet to Medina, he was as a teenager. During the time of the Prophet, he was honored by the titles of The Prophet’s servant, the chief of police and the bearer of the flag of Ansar in some of the Ghazwa, indicating that he was closely associated with the Prophet. When Imam Ali became the caliphate, Qays was one of the first to swear allegiance to him and to provide the preparations for the Jamal war with Imam Ali and even later, he was as one of the major commanders of Siffin and Nahrawan. Imam Ali initially chose him as the governor of Egypt, but was later dismissed for some reason. Then, Qays was chosen by the Imam Ali as the chief commander of the city guards and then assigned to the Azerbaijan province. Qays ibn Sa’d was the first to pledge allegiance to Imam Hassan and eventually settled in Medina after the peace of Imam Hassan and died at the end of Muawiyah’s rule. The present study has investigated the role and impact of Qays ibn Sa’d on historical events of the Prophet’s era and the era of Imam Ali and after them, using descriptive- analytical and historical resources. Our studies show that Qays and his family were the main pillars of Islam in the time of the Prophet and even after his death and in the time of Imam Ali. He has shown great interest in strengthening and consolidating Islam and has remained committed to his promise to the end.